Identification of Power Plant Operation and Loading Problems at Ngalau Baribuik Micro Hydro, Padang - Refdinal Nazir; Andi Pawawoi; Melda Latif; Muhammad Imran Hamid; Pinto Anugrah; Eka Fitrianto; Ahmad Ahmad (Jurusan Teknik Elektro, Universitas Andalas, 2021)
Ngalau Baribuik Micro-hydro Power Plant (MHP) is located in Bukit Karang Putih, Lubuk Kilangan, Padang City. This MHP with a capacity of 10 kW belongs to the local community which has been operating since 2012. This MHP was built with the aim of meeting the electricity needs of the people of Nagari Ngalau Baribuik who are not covered by electricity from PLN. Based on the information obtained from the MHP management, until now the operating profile and loading pattern of the MHP which is managed independently by the community has not been identified. To overcome this problem, a community service activity was carried out to minimize the failure of the MHP in meeting the needs of the community and the worst possibility was that there was damage to the generator. The target of this activity is the people of Nagari Ngalau Baribuik who are consumers of the MHP. Through this community service activity, the people who are consumers of the Nagari Ngalau Baribuik MHP have understood the importance of saving energy to maintain the sustainability of the MHP. People also know tips for saving energy that they can apply in their daily lives. Efforts to transfer knowledge to the community have been successfully carried out through this activity.